A Financial Conditions Index for Poland - Ho, Giang; Lu, Yinqiu (Washington, D.C. : International Monetary Fund, 2013)
This paper constructs a financial conditions index for Poland to explore the link between financial conditions and real economic activity. The index in constructed by applying two complementary approaches-factor analysis and vector auto-regression approach. We evaluate the index's forecasting performance against a composite leading indicator developed by the OECD. We found that the FCI is highly correlated with GDP growth, attesting to the importance of financial sector in Poland's economy. In-sample and out-of-sample forecasting exercises indicate that the FCI can outperform the CLI in predicting near-term GDP growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet